MAKNA RAGAM HIAS BINATANG PADA KLENTENG KWAN SING BIO DI TUBAN - Mulyono, Grace; Thamrin, Diana (Institute of Research and Community Outreach - Petra Christian University, 2008)
The Chinese culture is rich with symbols and meanings, particuliarly the ones related to living creatures. The Chinese society often draw relationships between the characteristics of animals to the values in life desired by mankind in order to achieve perfection. The temple is one of the places rich in Chinese animal symbolism. In the temple of Kwan Sing Bio Tuban, the application of animal symbolism is exceedingly prominent. The dragon, phoenix, unicorn, horse and other animals symbolize important values in life such as health, longevity, strength, wealth and protection. Abstract in Bahasa Indonesia: Budaya Tionghoa kaya akan makna dan simbol, khususnya yang berhubungan dengan mahluk hidup. Masyarakat Tionghoa sering mengkaitkan sifat-sifat hewan dengan nilai-nilai hidup menuju kesempurnaan yang diingini oleh setiap manusia. Klenteng merupakan salah satu tempat aplikasi budaya Tionghoa yang penuh dengan simbol mahluk hidup. Di klenteng Kwan Sing Bio Tuban, penerapan simbol mahluk hidup banyak sekali ditemukan. Naga (lung), phoenix (feng), unicorn (kili), kuda (ma) dan berbagai macam hewan lainnya melambangkan nilai-nilai kehidupan seperti kesehatan, panjang umur, kekuatan, kemakmuran, dan perlindungan. Kata kunci: makna, ragam hias, budaya Tionghoa, klenteng, mahluk hidup.